Completion lymphadenectomy for a positive sentinel node biopsy in melanoma patients is not associated with a survival benefit. Issue 8 (18th March 2019) - Klemen, Nicholas D.; Han, Gang; Leong, Stanley P.; Kashani‐Sabet, Mohammed; Vetto, John; White, Richard; Schneebaum, Schlomo; Pockaj, Barbara; Mozzillo, Nicola; Charney, Kim; Hoekstra, Harald; Sondak, Vernon K.; et al.
Abstract: Background: Completion lymph node dissection (CLND) for sentinel lymph node (SLN) disease in melanoma patients is debated. We evaluated the impact of CLND on survival and assessed for predictors of nonsentinel node metastasis (positive CLND). Methods: Positive SLN melanoma patients were retrospectively identified in the Sentinel Lymph Node Working Group database. Clinicopathological factors were correlated with CLND status, overall survival (OS), and melanoma‐specific survival (MSS). Results: There were 953 positive SLN patients of whom 831 (87%) had CLND. Positive CLND was seen in 141 (17%) cases and was associated with worse OS and MSS (both P  < 0.001). CLND was not performed (No‐CLND) in 122 of 953 positive SLN cases (13%), of whom 100 had follow‐up and 18 (18%) developed a nodal recurrence (NR). No significant differences in OS and MSS were seen comparing CLND with No‐CLND ( P  = 0.084, P  = 0.161, respectively) and comparing positive CLND with No‐CLND NR patients ( P  = 0.565, P  = 0.998, respectively). Gender, primary site, ulceration, and number of positive SLNs were correlated with nonsentinel node metastasis. Conclusions: Performance of CLND provides prognostic information but is not associated with a survival benefit. Clinical variables can predict a positive CLND in patients who may be at high risk of recurrence.